THE ROLE OF COMPUTER-ASSISTED INSTRUCTION IN ENHANCING COMPUTER LITERACY AMONG JUNIOR SECONDARY SCHOOL STUDENTS IN ENUGU STATE - Ene, Elizabeth U. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2022)
Computer technologies and their related resources are increasingly adopted in the educational ecosystem in Nigeria. The trend demands that every student possess essential computer knowledge to be aligned with modern-day teaching and learning. CAI has been widely used in teaching in Nigeria, but it is still unclear if the adoption of CAI can as well enhance computer literacy. The present study examined the role of CAI strategy in improving the computer literacy of junior secondary school students. A total of one hundred and eighty-seven secondary school students were drawn from eight public secondary schools in Enugu state as the study's participants. The study adopted a quasi-experimental pre-test and post-test study design. The result revealed a significant difference in student's computer literacy between the students taught with the CAI method and those taught with the conventional way at MD = 5.08, t (185) = 7.328, p = .000. Thus, the study concludes that a computer-assisted instructional method is an indispensable tool that could influence students' computer literacy, especially among secondary school students. The practical implications and recommendations are discussed.